2022
DOI: 10.3390/biomedicines10030539
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Benefits, Clinical Challenges, and Neuropathologic Promise of Medical Marijuana: A Systematic Review of Cannabinoid Effects in Multiple Sclerosis and Experimental Models of Demyelination

Abstract: Despite current therapeutic strategies for immunomodulation and relief of symptoms in multiple sclerosis (MS), remyelination falls short due to dynamic neuropathologic deterioration and relapses, leading to accrual of disability and associated patient dissatisfaction. The potential of cannabinoids includes add-on immunosuppressive, analgesic, neuroprotective, and remyelinative effects. This study evaluates the efficacy of medical marijuana in MS and its experimental animal models. A systematic review was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 212 publications
1
9
0
2
Order By: Relevance
“…A combination of agents that modify the course of the disease and have various effects on immunity is used for treatment at different phases of the disease. 4,5 Vitamin plus interferon therapy and the use of medical cannabis have also been studied as methods of treatment in MS. 6,7 This disease leads to a widespread demyelination caused by selective involvement of oligodendrocytes and axonal loss. Additional psychobehavioral symptoms such as anxiety, dementia and depression are also observed.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of agents that modify the course of the disease and have various effects on immunity is used for treatment at different phases of the disease. 4,5 Vitamin plus interferon therapy and the use of medical cannabis have also been studied as methods of treatment in MS. 6,7 This disease leads to a widespread demyelination caused by selective involvement of oligodendrocytes and axonal loss. Additional psychobehavioral symptoms such as anxiety, dementia and depression are also observed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of an A2A antagonist restored the inflammatory response, suggesting that CBD may play a role by binding with the A2A receptor ( Ribeiro et al, 2012 ). In addition, in the inflammatory model of demyelinating disease induced by encephalomyelitis virus, the application of CBD reduced leukocyte infiltration and activated microglia in the cerebral cortex, suggesting that CBD can limit inflammatory response by increasing adenosine signal transduction ( Longoria et al, 2022 ). Overall, we suggest that CBD can inhibit inflammation; however, whether it plays an anti-inflammatory role by binding to adenosine receptors to inhibit apoptosis needs further investigation.…”
Section: Cannabinoid Ameliorates Inflammatory Diseases By Regulating ...mentioning
confidence: 99%
“…The antalgic effect induced by cannabinoids may be partially explained by a central mechanism which involves the restoration of cortical pain gating mechanisms, most likely through the modulation of sensory–motor cortical integration [ 239 ]. In a systematic review published by Longoria et al, pain reduction was found at −3.42 points after cannabinoids administration when compared to a control group [ 240 ]. In another paper focusing on the effects of cannabinoids on MS neuropathic pain, Jones and collaborators identified a clinically relevant difference between placebo and treatment groups but without reaching statistical significance [ 241 ].…”
Section: The Interplay Between Cannabinoid System and Age-related Dis...mentioning
confidence: 99%